Role of oxylipins and small metabolites in pre-eclampsia - Sander, Katrin Natsumi (2016)
Pre-eclampsia affects about 5% of all pregnant women and is one of the most important pregnancy complications world-wide. Life threatening complications require an immediate medical management of pre-eclampsia. However, as the origin of this disease is still unexplained, diagnosis, treatment and management still pose a challenge.